The use of 585 and 1064 nm laser for the treatment of basal cell skin cancer - Rifat R. Saytburkhanov; Irina N. Kondrakhina; Xenia I. Plakhova; Alexey A. Kubanov (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
Background. Basal cell skin cancer is the most common malignant epithelial skin neoplasm in fair-skinned people and accounts for two-thirds of all skin cancers in this population. Tumor lesions have a supporting vascular network that serves as a target for vascular selective lasers. Aims. To assess the effects of laser radiation at a wavelength of 585 and 1064 nm on the vasculature of various forms of basal cell skin cancer using dermatoscopy and in vivo confocal microscopy. Materials and methods. The study included 20 patients with 20 lesions of histologically confirmed basal cell skin cancer treated with a pulsed dye laser (wavelength 585 nm) and a long-pulse neodymium laser (wavelength 1064 nm) in the conditions of the consultative and diagnostic center of the Federal State Budgetary Institution GNTSDK of the Ministry of Health RF in the period from 2021 to 2022. The effectiveness of therapy was assessed using non-invasive methods for examining the skin. Results. According to the results of the two-year follow-up period, 100% effectiveness of therapy in both groups is noted, in 2 patients treated with a neodymium laser, the formation of hypertrophic scars in the treatment area is noted. Conclusions. Treatment of patients with basal cell skin cancer with selective vascular lasers may be an effective treatment option. Additional studies with a larger sample of observations and a long monitoring period are needed to confirm the effectiveness of this treatment method.